Unusual side effects of levetiracetam. Issue 4 (26th April 2021) - Badarny, Samih; Badarny, yazid; Mihilia, Fatima
Abstract : We present a 75-year-old man who was admitted to our hospital due to 4 months of general deterioration, gait disturbance and cognition impairment which appeared very close to the start of levetiracetam (LEV) as a new antiepileptic drug. Brain CT shows central and less peripheral atrophy of brain, and diagnosis of normal pressure hydrocephalus was raised; however, removal of 30 cc of cerebrospinal fluid (CSF) by lumbar puncture in order to amend walking did not lead to gait improvement. After excluding metabolic, vascular, infection, inflammatory and other reasons explaining his status. Thinking that may be any correlation between LEV added in the last months and his clinical condition, we stopped LEV. Several days after that, there is marked improvement in his general sensation, alertness and cognitive status and there is marked improvement in walking balance to the point of being able to walk without the use of walker or cane or help from other person. Certain cognitive impairment and gait difficulties are not known as side effects of LEV treatment.